2021
DOI: 10.3390/ijerph18189877
|View full text |Cite
|
Sign up to set email alerts
|

Precarious Suicide Behavior According to Housing Price Gap: A Case Study on South Korea

Abstract: In 2018, the suicide rate in South Korea was the highest among the Organisation for Economic Co-operation and Development countries, and socioeconomic inequality has intensified. This study analyzes the impact relationship between suicidal impulses and economic inequality in South Korea. This study measures suicidal impulses thoughts National Health Survey Data and economic inequality based on the housing prices gap in the country. The primary analysis results were as follows: First, suicidal impulses were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Unlike other studies (Kang et al, 2021; Park et al, 2023), our study found no association between suicide and either housing prices or the housing price-to-income ratio. Instead, we found a correlation solely with the housing rental index.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other studies (Kang et al, 2021; Park et al, 2023), our study found no association between suicide and either housing prices or the housing price-to-income ratio. Instead, we found a correlation solely with the housing rental index.…”
Section: Discussioncontrasting
confidence: 99%
“…Certain researchers have explored the impact of house loss on suicide rates, particularly in the aftermath of the global subprime mortgage crisis (Fowler et al, 2015; Jones & Pridemore, 2016; Rojas & Stenberg, 2016). Others have focused on the correlation between housing-price-related indices and suicide (Berk et al, 2006; Kang et al, 2021; Park et al, 2023). However, in studies using housing-price-related indices, each employs a unique, singular index, such as the housing price index (Kang et al, 2021), housing loan interest rates (Berk et al, 2006), or the housing cost-to-income ratio (Park et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study suggest that an unequal environment is related not only to severe mental disorders such as traumatic stress, suicidal ideation, and depression, but also to the stress commonly felt in daily life. As per Durkheim [ 78 ] and Wilkinson’s [ 79 , 80 ] hypothesis, economic inequality is related to mental disorders, and previous studies have empirically analyzed inequality with traumatic stress [ 20 ], status anxiety [ 17 ], depression [ 11 , 21 ], and suicidal ideation [ 9 ]. Although the mental health problems in previous studies are close to severe mental illness, the daily stress in this study is a mild mental health problem felt in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…A society with a Gini coefficient close to 0 means a society with small economic disparity among its members, and a society with a Gini coefficient close to 1 means a society with large economic disparity among its members. Although the Gini coefficient was designed to measure income disparity, the index is also used to measure disparity and distribution in diverse fields [ 60 ] in housing price distribution [ 9 , 61 ], happiness inequality [ 62 ], and bacterial aggregation [ 63 ]. Based on the basic principle of the Gini coefficient, this study calculated the regional economic inequality index by accumulating housing prices from the lowest to the highest by replacing income.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation